PSYCHOLOGICAL FACTORS AFFECTING STUDENTS’ACHIEVEMENT IN COLLEGE ALGEBRA IN THREE IDENTIFIED CAMPUSES AT THE CSCST SYSTEM: LEARNING EXERCISES - Velos, Severina P (Journal of Agriculture and Technology Management; Tropical Technology Journal Volume 11 No. 1-2, 2008, 2008)
This study aimed to assess the psychological factors affecting students’ achievement in College Algebra in the three identified campuses at the CSCST System particularly: Main Campus, Argao Campus, and Moalboal Campus for academic year 2006-2007. It focused on the following aspects: 1) level of difficulty in College Algebra as to comprehension, application, and analysis skills. 2) The profile of the internal and external psychological factors that caused such as difficulties with respect to student’s attitude, content, teacher, and learning atmosphere factors, and 3)The degree of relationship of both psychological factors to students’ performance. This is a descriptive research using four sets of instruments administered to two hundred thirty-six (236) students. The data were interpreted using mean, standard deviation, ranking, index of difficulty, Spearman rho, and the t-test. A great percentage of the respondents found College Algebra a difficult subject. They were most deficient in application and analysis skills on the following contents: Functions and Relations, Inequalities, Exponential and Logarithmic Functions, Permutation Combination and Probability, Solutions of Equations and Associated Word Problems. Only those who belong to the average group perceived the fairly agreeable attitude towards the subject. Consequently, there is significant relationship on students’ achievement and attitude, content, teacher and learning atmosphere factors. Majority of the freshmen students of the three campuses had only satisfactory performance and were deficient on higher level thinking skills that could be traced on both internal and external psychological factors. It is recommended that the learning exercises be adopted to enhance student’s performance in college algebra.